Kino, czytelnik i czytający. O Geniuszu Michaela Grandage’a - Zwierzchowski, Piotr (Przestrzenie Teorii, 2019)
Zwierzchowski Piotr, Kino, czytelnik i czytający. O Geniuszu Michaela Grandage’a [The Cinema and Two Types of Readers. About Michael Grandage’s Genius]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 371–381. ISSN 1644-6763. DOI 10.14746/pt.2019.32.20. In Genius (2016) by Michael Grandage books are present in many ways. The main characters are William ‘Max’ Perkins, an editor of the Charles Scribner’s Sons publishing house and Thomas Wolfe, a writer starting out at the time. The film is concerned with their relationship and the creation of the novel. The book functions as both a work and an artefact (also as typescript). Literature is a conversation topic and a way of living. One of the most important spaces is the publishing house building. Piotr Zwierzchowski, however, analyses Genius primarily as a contribution to reflections on the act of reading and its film visualization, referring to the distinction introduced by Alberto Manguel (modelled on Barthes’ écrivain and écrivant) between the reader as someone who reads “with no ulterior motive” and one “for whom the text is a vehicle towards another function”.